Importance of Magnesium Sulphate in Improvement of GCS Score after Severe Traumatic Brain Injury - Muhammad Asim Khan Rehmani, Shiraz Ahmed Ghouri, Farrukh Zulfiqar, Muhammad Faaiq Ali, Qazi Muhammad Zeeshan, Ramesh Kumar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Grounded on a series of studies, magnesium Sulphate (MgSO4) administered after extensive axonal damage has emerged as a valuable neuroprotective mediator. This study was held to investigate whether magnesium Sulphate had therapeutic safety and efficacy in patients with severe diffuse axonal injury and its effect on improving GCS scoring. Methods: This double-blind, randomized and placebo-controlled clinical trial study was held from October 2020 to September 2021, patients with severe extensive damage to the axons were studied who presented to the Neurosurgery emergency of tertiary care hospital, and written knowledgeable permission was taken from all subjects. 42 patients who met the eligibility criteria were randomly assigned to our study. Adult patients with severe diffuse axonal injury within the first hour of closed traumatic brain injury (TBI) and meeting eligibility conditions were divided randomly into 2 groups. The treatment regimens contained preliminary intravenous 50 mg / kg magnesium sulfate as loading dose within one hour of injury, followed by QID 50 mg / kg magnesium sulfate up to 24 hours post-injury. The results were mortality, GCS, and assessment of motor function up to two-months after injury. Results: Magnesium had a substantial optimistic impact on GCS after two-months (P = 0.04). The result of motor function improved more in the MgSO4 group than in the control group, but it was not statistically important (p = 0.52). Finally, it is concluded that direction of magnesium sulfate after severe DAI can play a neuroprotective role.